HUBUNGAN KOMPETENSI PEDAGOGIK DAN MOTIVASI MENGAJAR DENGAN PRODUKTIVITAS GURU IPA SMP NEGERI SE-KABUPATEN LAMPUNG TIMUR - Sulistiyani, Sulistiyani (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Professional teachers are teachers who have competence to support their tasks that teachers can achieve high productivity. Factors related to teacherâs productivity include pedagogic competence and teaching motivation. The aims of this research are want to know: (1) relationship between pedagogic competence with productivity (2) relationship between teaching motivation with productivity (3) relationship between pedagogic competence and teaching motivation together with productivity . The population of this research were all science teachers those be civil servants at SMP in East Lampung District in the school year of 2013/2014 as many as 168 people, and samples 63 teachers. The instrument used was a questionnaire that had been tested for validity and reliability. The data analysis used was the technique of correlation and simple regression analysis on the first and second hypothesis testing, and regression analysis technique on the third hypothesis testing. Based on the theoretical studies and findings of data analysis both partially and simultaneously, it can be concluded that pedagogic competence and teaching motivation positively and significantly associated with productivity of Junior High School Science Teachers in East Lampung District. The benefits of this research as an input for principals and supervisors who act as a motivator, facilitator, and dynamisator to enhance the pedagogic competence and teaching motivation by providing opportunities to follow activities such as training, workshops, or seminars in order to increase productivity.Kata Kunci: kompetensi pedagogik, motivasi mengajar, produktivitas guru